Comparative Cranial Joint Variation in Three Different Lizards: Impact of Feeding Habit - Elif Yıldırım Caynak; Kamil Candan; Yusuf Kumlutaş; Ahmet Gökay Korkmaz; Sezen Birlik; Dudu Mertgenç Yoldaş; Serkan Gül; Çetin Ilgaz (Life)
The skull structure in vertebrates is closely related to feeding mode. This study examines the relationship between the cranial joint morphology variation among different lizard species [Eumesces schneideri (Daudin, 1802), Anguis colchica (Nordmann, 1840), and Eremias suphani (Başoğlu & Hellmich 1968)] and their feeding habit. This study investigates the cranial anatomical correlates of distinct cranial kinesis models. Different cranial joints permitting intracranial mobility have been observed among these species using histological section and whole-mount techniques. The cranial joints are similar among species that generally exhibit cranial kinesis. The stomach contents of the species were analyzed, and E. schneideri has the highest prey diversity among the examined species, followed by E. suphani and A. colchica in that order. The study indicated that the prey preferences differ among three lizard species. While no plant material was detected in the stomach contents of E. suphani and E. schneideri, it was detected in A. colchica. The diet of the three lizards consisted of various species of small arthropods such as Arachnida, Lepidoptera, Coleoptera, Formicidae, and Gastropoda. Additionally, no significant differences were detected in SVL, head, and jaw size measurements between adult males and females of each species.